ФІСКАЛЬНИЙ МЕХАНІЗМ: СУТНІСТЬ, ІНСТРУМЕНТИ ТА ПРИНЦИПИ ЙОГО ДІЇ - Канцур, Інна Григорівна (Науковий журнал «Світ фінансів», 2017)
Канцур І. Г. Фіскальний механізм: сутність, інструменти та принципи його дії. З’ясовано, що з метою формування і розподілу фінансових ресурсів держава використовує перерозподільчу функцію податків та бюджету, за рахунок чого впливає на забезпечення соціальних гарантій населення, забезпечення зайнятості, підвищення рівня доходів населення, фінансування та розвиток соціальної сфери тощо. Доведено, що фіскальний механізм виступає інструментом впливу держави на соціально-економічні процеси. Розглянуто сутність фіскального механізму як сукупність бюджетного та податкового механізмів, між якими існує тісний взаємозв’язок. Проаналізовано дію фіскального механізму, яка проявляється через його інструменти та принципи. Канцур И. Г. Фискальный механизм: сущность, инструменты и принципы его действия. Установлено, что с целью формирования и распределения финансовых ресурсов государство использует перераспределительные функции налогов и бюджета, за счет чего влияет на обеспечение социальных гарантий населения, обеспечение занятости, повышение уровня доходов населения, финансирование и развитие социальной сферы. Доказано, что фискальный механизм выступает инструментом влияния государства на социально-экономические процессы. Рассмотрена сущность фискального механизма как совокупность бюджетного и налогового механизмов, между которыми существует тесная взаимосвязь. Проанализировано действие фискального механизма, которое проявляется через его инструменты и принципы. Kantsur I. Fiscal mechanisms: the essence, tools and principles of its actions. Introduction. With a view to the formation and distribution of financial resources the state uses redistributive function of taxes and the budget, thus affects the social security of population, employment, increasing income levels, financing and development of social sphere. Fiscal mechanism is an instrument of state influence on socio-economic processes. Depending on the socio-economic conditions in the country it needs constant improvement, which necessitates deeper theoretical study of the mechanism of fiscal nature and principles of action.Purpose. The purpose of this article is to study the essence of the concept of “fiscal arrangements” tools of its impact on social development and principles of action.Results. The essence of a fiscal mechanism as a set budget and tax mechanisms, among which are closely interrelated. After all, the tax mechanism affects the formation of budget revenues, balances its revenues and expenditures affecting the dynamics of socio-economic development. It was established that the effect of fiscal mechanism manifested through its tools and principles. As instruments of fiscal mechanism, we consider some tools that are used by the state to perform its functions, that is specific methods of influence on the process of budget resources, their allocation and efficient use, encouraging or limiting the nature of the action. The principles of fiscal mechanism, in our opinion, include: the principle of consistency, objectivity, balance (proportionality, harmony), feasibility and argumentation, timeliness, effectiveness and efficiency, social equity, target orientation, responsibility, self-financing, information content and availability. The author’s principles of fi scal mechanism aimed at ensuring the implementation of both fiscal and social function, formation of budget revenues and regulation of social and economic processes in the country, thus satisfying the social needs and social development.Conclusion. Consequently, the fiscal mechanism should be flexible in order to best meet the needs of the state and the needs of society, effectively redistributing income among different groups of people, the well-being of the population using social orientation of budget expenditures and ensure social justice. That is, it is a means of ensuring balanced socio-economic development of the country, using their tools should provide a level of tax revenue, allowing the development of social components in the system of social benefits.